Implementation of the Health Operational Assistance Fund (BOK) at the Pasundan Community Health Center in Samarinda City - Yuliana; Masjaya; Daryono; Fajar Apriani; Mohammad Jamal Amin (Green Publisher Indonesia, 2026)
Implementation of Health Operational Assistance Fund (BOK) at the Pasundan Health Center, Samarinda City under the guidance of Prof. Dr.H.Masjaya, M.Si as supervisor I and Daryono, M.Si., Ph.D as supervisor II. This study aims to examine the implementation of the Health Operational Assistance Fund (BOK) at the Pasundan Health Center in Samarinda City and identify supporting and inhibiting factors in its implementation. The research method uses a descriptive qualitative approach with data collection techniques through interviews, observations, and document analysis. The results of the study show that the implementation of the BOK Fund has not been optimal. The budget absorption for the 2021-2024 period did not reach 100% and the implementation of activities is still constrained by administrative aspects, limited human resources, and ineffective reporting and evaluation systems. Supporting factors are in the form of clear regulations and implementation commitments, while inhibiting factors include disbursement delays, coordination that has not been maximized, and high workload. This study emphasizes the need to improve the quality of planning, coordination effectiveness, and strengthening utilization and evaluation to increase the effectiveness of the use of BOK Funds in supporting basic health services.